Leminski : poética da lemniscata - Oliveira, Marco Aurélio Furno (2015)
Due to the studies about the theme multiplicity of the Leminski poetic, truly polyhedral, we based on the seventeenth poem from the book named Caprichos & relaxos, “Ali só ali se”, because it is a rich example of intertextuality, poetic-linguistic luddite and metapoetry and by presenting issues concerning the language based on the philosophy of the ancient stoicism, mainly the slide on the meaning and senses according to the Gilles Deleuze optics about the Logic of Sense.